Effects of rosemary essential oil as a feed additive on performance, rumen fermentation, and blood parameters in preweaning Holstein calves: - Biyik, F; Biricik, H; Urkmez, E; Kara, C; Cetin , I; Udum, D (Journal of the Hellenic Veterinary Medical Society, 2023)
The objective of this study was to investigate the effects of rosemary essential oil (REO) supplementation on growth performance, some blood metabolites and rumen fermentation in calves throughout the suckling period. Fourty Holstein calves were randomly divided to four dietary groups. Each group consisted of 10 calves; control with no REO supplementation (CON), supplementation of 500 mg/d REO (REO1), supplementation of 1000 mg/d REO (REO2) and supplementation of 2000 mg/d REO (REO3). REO supplementation quadratically increased (P<0.05) the calf starter (CS) intake, average daily gain (ADG) and feed efficiency. Calves fed REO1 and REO2 had the highest CS intake and ADG. Ruminal ammonia-N concentration was lower (P=0.02) for calves fed REO3 than calves fed REO1, but total volatile fatty acids concentration was higher (P<0.01) for calves fed REO1 compared with calves fed CON and REO3. The concentrations of ghrelin, NEFA and BHBA increased linearly (P<0.05) with increasing levels of REO. Calves fed REO2 and REO3 had the highest concentration of ghrelin. Cholesterol concentration decreased linearly (P<0.01) with increasing REO levels on d 56. Calves fed REO2 and REO3 had the lowest cholesterol concentration. Also, serum IgG concentration was higher (P<0.01) in calves fed REO2 and REO3 compared with calves fed CON on d 28. It was concluded that the addition of different amounts of rosemary essential oil can positively change some rumen and blood metabolites of calves, as well as the supplementation of REO may have a beneficial effect on growth performance by increasing ghrelin.